1996
DOI: 10.1021/ma951667m
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Weight Distributions in Nitroxide-Mediated Living Free Radical Polymerization:  Kinetics of the Slow Equilibria between Growing and Dormant Chains

Abstract: A kinetic approach, recently developed to calculate the effect of exchange between a dormant and an active species in group transfer polymerization (GTP), has been applied to living free radical polymerization moderated by nitroxide stable free radicals. A general solution for the molecular weight distribution as a function of conversion has been derived. The solution depends only on the rate constants for propagation, the trapping of the growing chains by nitroxide radical, and the release of the growing chai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
0
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(76 citation statements)
references
References 16 publications
1
74
0
1
Order By: Relevance
“…[6,[9][10][11] Finally, test 3 shows that the results are in agreement with the expert's opinion. However, the value of test 3 for [N] is arguably very close to 2 and thus indicates that the expert's opinion about the nitroxide concentration was not overly accurate.…”
Section: Resultssupporting
confidence: 61%
“…[6,[9][10][11] Finally, test 3 shows that the results are in agreement with the expert's opinion. However, the value of test 3 for [N] is arguably very close to 2 and thus indicates that the expert's opinion about the nitroxide concentration was not overly accurate.…”
Section: Resultssupporting
confidence: 61%
“…[51,52] Direct determination of capping constants by flash photolysis has also been described. [53] k deact together with K eq , determined above, allow the computation of the corresponding kinetic constant of activation…”
Section: Numerical Integration Softwarementioning
confidence: 99%
“…There have been a number of studies on kinetic simulation of living radical polymerization processes (14,19,68,69). In 1990 we (14) reported a study of the alkoxyamine-initiated polymerization which demonstrated the potential of this chemistry (13) for the production of narrow polydispersity polymers.…”
Section: Kinetic Simulation Of Controlled-growth Free-radical Polymermentioning
confidence: 99%